Comparative analysis of RANS and DDES methods for aerodynamic performance predictions for high performance vehicles at low ground clearances - Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Brighton, James (Cranfield University, 2023)
Various assessments of RANS and Hybrid RANS-LES turbulence models have been conducted for automotive applications. However, their applicability for high performance vehicles which exhibit much more complex flow phenomena is not well studied yet. In this work, the predictive capabilities of RANS and DDES models are investigated through a comparative study on a high performance configuration of the DrivAer Fastback model at a low ground clearance in an open road computational domain. The results show much agreement in the general pressure distribution, except in areas of highly unsteady flow. Visualisation of the flow field depicts that the DDES simulation is able to capture a wider range of turbulent scales with a higher fidelity. Lastly, variation in the magnitude, distribution and decay of pressure losses in the wake are observed between both simulations. The presented results are used to illustrate the capabilities and limitations of these turbulence models for other academic or industrial users to make an informed decision on the turbulence model suited for their objectives.
Keywords: Hybrid RANS-LES; DDES; RANS; DrivAer; High-Performance